Sikap terhadap Kesehatan Lingkungan Masyarakat Ditinjau dari Kondisi Sosial Ekonomi dan Tingkat Pendidikan - Supriyadi Supriyadi (Universitas Sebelas Maret, 2004)
The aims of this research is to answer the problem whether there are: 1) influence of the social economical condition of the village towards an attitude of the environmental health; 2) influence of the level of the educational background towards an attitude of the environmental health; and 3) interaction between social economical condition of village and the level of educational background in influencing an attitude towards environmental health. All the researches are applied to the Majaksingi society, Borobudur Sub District, Magelang Regency.The survey method and sampling technique of the research is done by the method of multistage ramdom sampling. The instruments to obtain the data are: 1) questionnaire in the form of Likert scale to measure and attitude towards the environmental health; 2) poll to distinguish the social economical condition of village and the level of educational background of the society. The technique of data analysis is employing Two Way Anova, with Factorial 2x2 designs. Before the process of data analysis, there is a test of analysis requirement by employing Normality Distribution Sample Test and Homogeneity Varian Test.Based on the research result, it is suggested that the social economical condition in less advanced village must be increased by applying the government program which cover the effort to increase the economical condition and to omit the negative social habits which can harm the environmental health. Beside that, the educational level of the society in isolated village in Menoreh Tenggara Majaksingi village must be given on opportunity to increase it. Only employing that way, their attitude toward enronmental health will rise up, and hopefully their environmental health will better. By knowing that there is no interaction between social economical condition of the village and the level of educational background, it indicated tha the theory of interaction cannot be applied to the two variables which have big influence towards the environmental health. The two variables do not depend on each other.